THE DIFFERENCE OF HEALTH EDUCATION THROUGH DEMONSTRATION AND SINGING VIDEO METHODS ON HAND-WASHING SOAP SKILL IN PRESCHOOL CHILDREN - Lestari, Indah; Krisnanto, Paulinus Deny; Fitriana, Lala Budi (Universitas Respati Yogyakarta, 2020)
The importance of hand cleanliness needs to be paid attention by preschool-aged children in order not to become disease germs? medium of transfer, such as diarrhea. Health education is needed to improve children?s skills in washing their hands. The demonstration method can get students actively involved while paying attention to the lesson being explained, and singing video media can encourage a learning motivation through interesting graphic displays and lyrics about the steps to wash the hands. To determine the difference between health education using demonstration and singing video methods? influence on preschool-aged students? handwashing with soap skills. This is quasi-experiment research which used a pretest and posttest nonequivalent control group. There were 24 samples involved as respondents, divided into two groups which consist of 12 students each. Bivariate tests for both the demonstration and the video methods were conducted using a paired t-test. A difference test between the demonstration and the video methods was conducted using an independent t-test. The average score for the demonstration method before the intervention was 39.5 and after the intervention was 90.2; the average score for the singing video method before the intervention was 47.5 and after the intervention was 89.9. Results of the difference test between pretest and posttest in the demonstration method group showed a p-value = 0.000, and the singing video method showed a p-value = 0.901.There was no score difference for handwashing wiwith soap skills. The use of demonstration and singing video methods were equally effective in improving handwashing with soap skills.